ESSENTIAL VIOLENCE AND RENÉ GIRARD’S MIMETIC THEORY - Johnsen, William A. (Homo Mimeticus II, 2024)
In La Rovina di Kasch , Roberto Calasso tagged René Girard as a hedgehog (1983, 205-10) using Archilochus’s distinction between knowing many things and one thing.¹ For Calasso, Girard’s one thing was the scapegoat mechanism. Girardians have inevitably increased this number to at least two, to include Girard’s mimetic theory as well as his Christian conversion as an epistemology (Kirwan in Girard, 2008, xii-xiii). In my title I have called attention to a less-recognized feature of violence as discussed within Girard’s "mimetic theory" to feature what Girard called in La violence et le sacré "la violence essentielle" (1972, 332).